Pemanfaatan Internet sebagai Sumber Belajar Mahasiswa - M. Husaini, M. Husaini M. Husaini (BINA' AL-UMMAH, 2017)
The presence of the internet has changed most of the way of life and everyday human activities. Students can use the internet as an alternative learning resource other than books to get more information. Along with the change of learning paradigm, the success of teaching and learning activities in universities is not only determined by the faculty / lecturer, but is greatly influenced by the liveliness of the students. Through the internet students can access the various literature and reference science needed quickly, so it can simplify the process of study.The problem of this research is how the pattern of internet utilization by da’wah management students, the extent to which the use of the internet as a learning resource for da'wah management students and what factors support student da'wah management utilize the internet as a source of learning. This research is a qualitative research with research location at Faculty of Da'wah and Communication Science UIN Raden Intan Lampung. The focus of this study includes students in using the internet, how far students use the Internet as a source of learning and factors that support students in using the internet as a source of learning. Data collection techniques in the form of data collection through interviews and observation. Examination of the validity of the data used is triangulation technique. Data analysis used is descriptive qualitative.The results showed that all students of da'wah management have known and used the internet. Each student has different ways of using the internet such as where to access, internet access, and also sites accessed by students. Where to access the internet that is often used by students in the cafe, at home, and in the neighborhood around the campus. Dakwahmanagement students utilize the internet as a source of learning, because with the internet can facilitate in finding information and course assignments. Factors supporting the utilization of the internet as a source of student learning, among others, demands from lecturers to meet the tasks of courses, learning resources available on the internet more complete, assist in getting reference courses, make it easier to do tasks, information is more clear and valid, faster in the search for information, a more complete source of knowledge, the existence of hotspot facilities on campus, up to date / new news, cheaper cost, easy access, curiosity and needs.Conclusion from this research that is student of da'wah management have their own way in utilizing internet. Lecture demands and ease of accessing information are the factors driving respondents using the internet as a source of learning. Based on the results of research that has been done, suggestions that the authors convey related to the results of this research is for the UIN Raden Intan Lampung to provide internet services in the library of the Faculty of Da'wah and Communication Studies. For UIN Raden Intan Lampung to expand the hotspot area in the campus so that students can more easily access the internet. To the management of da'wah da'wah faculty of science and communication science to use internet facility as learning resource.